Towards enhancing light harvesting - Subphthalocyanines as electron acceptors - Nieto, Carlos Romero; Medina, Anais; Molina-Ontoria, Agustin; Claessens, Christian G.; Echegoyen, Luis; Martin, Nazario; Torres, Tomas; Guldi, Dirk Michael (Chemical Communications, 2012)
One carbon atom is too many. Two subphthalocyanine-extended TTF electron donor-acceptor conjugates were synthesized and characterized. Their photophysical properties prompt the remarkable impact that one extra carbon between the two constitutents exerts on photoinduced processes, that is, charge recombination dynamics in the normal versus inverted region. © The Royal Society of Chemistry 2012.